Frankenstein: A Literary Perspective on the Coronavirus Pandemic - Aldowkat, Issam M.; Abu-Snoubar, Tamador K.; Olimat, Sameer N.; Mahadin, Dana K.; Rababah, Mahmoud A. (Jordan Journal of Modern Languages & Literatures, 2024)
This paper examines how Mary Shelley’s Frankenstein, building on Stanley Fish’s reader-response theoretical insights in “interpretive communities”, shapes the readers’ reception of the novel coronavirus pandemic. It argues that tagging the virus as the “Frankenstein virus” is informed by imaginative resemblances between the narratives of Victor Frankenstein’s scientific engagement and the coronavirus pandemic. Therefore, referencing Frankenstein nowadays underlines the terror that is haunting the public imagination upon the coronavirus outbreak and its mutations into more lethal variants. It also reveals how the novel makes its readers susceptible to promote the hypothesis on the coronavirus’s human engineering and manipulation. The paper also explains how Frankenstein manages the contagion embedded in Victor’s monster by ‘othering’ it, which helps the reader recognize the importance of the preventive measures, such as self-distancing and stay-at-home orders to downplay the spread of the virus and promote the psychological and physical wellbeing of the public.